High folate and low vitamin B12 status during pregnancy is associated with gestational diabetes mellitus. Issue 3 (June 2018) - Lai, Jun S.; Pang, Wei Wei; Cai, Shirong; Lee, Yung Seng; Chan, Jerry K.Y.; Shek, Lynette P.C.; Yap, Fabian K.P.; Tan, Kok Hian; Godfrey, Keith M.; van Dam, Rob M.; Chong, Yap Seng; Chong, Mary F.F.
Summary: Background & aims: B-vitamins and homocysteine may contribute to the development of gestational diabetes mellitus (GDM), but existing studies are inconsistent. We examined the cross-sectional associations of plasma folate, vitamins B6, B12, and homocysteine concentrations with GDM and glycemia in a sample of multi-ethnic Asian pregnant women. Methods: Plasma concentrations of folate, vitamins B6, B12, homocysteine and glucose were measured at 26-weeks' gestation in 913 pregnant women. GDM was diagnosed using the 1999 World Health Organization criteria. Associations were examined with linear or logistic regression, adjusted for confounders and stratified by ethnicity. Results: Higher plasma folate was associated with higher 2-h glucose and higher odds of GDM [0.15 (0.02, 0.23) per 1-SD increment in folate, OR 1.29 (1.00, 1.60)], mainly among Indian mothers. Higher plasma vitamin B12 and homocysteine were associated with lower fasting and 2-h glucose, and lower odds of GDM [−0.04 (−0.07, −0.01) per 1-SD increment in B12 and −0.09 (−0.18, −0.003) respectively, OR: 0.81 (0.68, 0.97); −0.05 (−0.08, −0.02) per 1-SD increment in homocysteine and −0.12 (−0.21, −0.02) respectively, OR: 0.76 (0.62, 0.92)]. The highest odds of GDM were observed among women with combined vitamin B12 insufficiency and high folate concentration [OR: 1.97 (1.05, 3.68)]. An association between higher vitamin B6 and higher 2-h glucose shifted towards null adjusting for other B-vitamins. Conclusions: Higher maternal folate coupled with vitamin B12 insufficiency was associated with higher GDM risk. This finding has potential implications for antenatal supplement recommendations but will require confirmation in future studies.